Fedón, 69c:: ¿por qué los Î²Î¬ÎºÏ‡Î¿Î¹ son los verdaderos filósofos? - Bernabe, Alberto (Revista Archai, 2015)
Abstract: The paper analyses Phaedo, 69c, with the aim of answering two questions: 1) why Socrates quote an Orphic text, specifying that it has a hidden meaning (Î±á¼°Î½Î¯Ï„Ï„ÎµÏƒÎ¸Î±Î¹), and 2) how he comes to the conclusion that men called Î²Î¬ÎºÏ‡Î¿Î¹ by the Orphics are the true philosophers. The repeated alusion to “risk” (ÎºÎ¯Î½Î´Ï…Î½Î¿Ï‚, ÎºÎ¹Î½Î´Ï…Î½ÎµÏÏ‰) in the dialog is pointed out and the procedure of Î±á¼°Î½Î¯Ï„Ï„ÎµÏƒÎ¸Î±Î¹ (a sort of codifying poetic text) as a symbolic manner of referring to deep truth is analysed. On the other hand, it is highlighted how the philosopher considers that requirements for salvation in the Ï„ÎµÎ»ÎµÏ„Î±Î¯ (to be Î¼ÎµÎ¼Ï…Î·Î¼ÎÎ½Î¿Ï‚, ÎºÎµÎºÎ±Î¸Î±ÏÎ¼ÎÎ½Î¿Ï‚, Ï„ÎµÏ„ÎµÎ»ÎµÏƒÎ¼ÎÎ½Î¿Ï‚, Î²ÎµÎ²Î±ÎºÏ‡ÎµÏ…Î¼ÎÎ½Î¿Ï‚) can only be really reached practising philosophy. Keywords: Plato, Phaedo, symbolic language, salvation.